Quality of Life and Psychological Adjustment of Women Living with 46, XY Differences of Sex Development. (20th April 2015) - D'Alberton, Franco; Assante, Maria Teresa; Foresti, Maura; Balsamo, Antonio; Bertelloni, Silvano; Dati, Eleonora; Nardi, Laura; Bacchi, Maria Letizia; Mazzanti, Laura
Abstract Background Progressive care improvement for differences of sex development (DSD), regarding diagnosis communication, psychological, medical and surgical management has been claimed. Aim of the study To assess clinical management, quality of life (QoL) and the general psychosocial adjustment of individuals with 46, XY DSD. Some differences related to age at diagnosis are investigated. Design Cross‐sectional study using standardized questionnaires. Population Forty‐three Caucasian females with 46, XY DSD (self declared diagnoses: complete androgen insensitivity syndrome, n = 34; complete gonadal dysgenesis, n = 1; 5α‐reductase deficiency, n = 4; Leydig cell hypoplasia, n = 1; unknown diagnosis, n = 3; age years: 31.5 ± 9.6 [range 18–57 years]). Setting University Hospitals. Methods Subjects were required to fill in questionnaires (ABCL, WHOQOL, dedicated 17‐item questionnaire). Academic and socioeconomic data were compared with those of the Italian population. QoL and psychological data were compared with those of a comparison group (46, XX healthy females: n = 43; age, years: 34.5 ± 9.7, range 22–51years). Results Present sample of women living with 46, XY DSD were well adapted and were higher achievers than controls, both in educational and professional life. They showed good QoL, but they appeared less satisfied in psychological and social areas. They had borderline mean scores and statistically higher scores than the comparison group for depression, anxiety, internalizing and externalizing problems. Younger persons living with a 46, XY DSD showed better psychosocial adjustment than older ones. Younger women showed lower age at diagnosis communication. Psychological support was more often proposed at the time of diagnosis communication to younger individuals, and they undertook it more frequently than older ones. Conclusions Italian people living with 46, XY DSD were well adapted and successful; they reported a good QoL but showed higher degree of psychological distress than the comparison group. Lower psychological distress in younger women could indicate some positive effects of changes in management. D'Alberton F, Assante MT, Foresti M, Balsamo A, Bertelloni S, Dati E, Nardi L, Bacchi ML, and Mazzanti L. Quality of life and psychological adjustment of women living with 46, XY differences of sex development. J Sex Med 2015;12:1440–1449.